ANALISIS KELAYAKAN INVESTASI PADA MESIN CONE CRUSHER: Studi Kasus: CV. Pasir Mas Barkah Desa Sendangwaru Kecamatan Kragan Rembang Jawa Tengah - Ahmad Alifian Mighfar; Zainal Arief (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Rembang Regency is one of the areas located on the north coast in Central Java Province. The population of Rembang Regency based on the Central Statistics Agency in 2021 is 647,766 people. The main commodities of Rembang Regency are Agriculture and Fisheries. The sector that is also the mainstay of Rembang Regency is Mining, where the existence of a cement factory is one of the factors influencing the rapid development of the mining sector in Rembang Regency. CV Pasir Mas is a split stone company that serves the milling and sales of split stone from Sendangwaru Village, Kragan District, Rembang Regency. Since 2000 it has been producing split stones but using traditional methods, namely by using human power to break stones into split stones. In this modern era, the role of the modern stone crusher is so vital that the Cone Crusher machine is very useful in the production and sale of split stone in CV. This Mas Sand. The method used by the authors in this study is the Net Present Value (NPV), Internal Rate of Return (IRR), PP Payback Period, Profitability Index (PI) and Declining Balancing (DB) methods. The author conducted a survey by calculating the amount of income, the cost of buying the machine, the cost of installing the machine, the cost of mobilizing the company, the cost of purchasing raw materials, the cost of employee salaries and the expenses for maintaining machines and vehicles involved in the split stone production process. The results of the research show that the income is Rp. 5,288,141,000 annually, the NPV is Rp. 28,269,860,435. for an IRR of 9.04%, for a PI of 5.28 and depreciation of 1/5 every year the price of the Cone Crusher machine is Rp. 1,000,000,000, which means that in the first year there is a machine depreciation of Rp. 200,000,000